CD40-signalling abrogates induction of RORγt+ Treg cells by intestinal CD103+ DCs and causes fatal colitis - Christian Barthels (Nature Portfolio, 2017)
CD103+ dendritic cells induce iTreg cells to maintain immune balance in the gut, but how CD40-signalling regulates this process is unclear. Here the authors show that mice with constitutive CD11c-specific CD40-signalling have altered CD103+dendritic cell migration, reduced iTreg cell induction, and fatal colitis.